ASSESSMENT OF RECRUITMENT PRACTICE ON ORGANISATION PERFORMANCE: EMPIRICAL STUDY OF HOSPITALITY BUSINESSES IN ABUJA - Abomeh, Ofobruku Sylvester; Blessing C., Iheabunike Okafor (European Scientific Journal, ESJ, 2013)
This study assesses the impact of recruitment practices on the organisation performance in the hospitality industry in Abuja. The effectiveness of recruitment practices in the process of procurement of the most suitable employee that would enable hospitality business to achieve her organisational objectives is pertinent to this research study. The present inability of hospitality business to attract and engage best suitable employee with the right knowledge skills and altitude to steer the day to day operation of the business, high turnover of hospitality employee and how best recruitment practices can impact positively on organisation performance in the hospitality industry is the major focus of this research. The hospitality business fall into three major categories of hospitality business grading (five star, three star, and one star) by the Nigeria tourism development corporation. Data were collected from twelve hospitality organizational units cutting across directors, managers, and supervisors, through a survey questionnaire carried out in hospitality facilities made of four numbers each of the three different grade of the hospitality industry in Nigeria (five star, three, one). Data gathered were analysed using weighted mean factor. The study recommended that for hospitality business to be successful it must adhere to keeping good staff, gain employee and guest/customers loyalty that improve their market share, this can be achieved through the employment of best practice in employee recruitment.